Phytochemical profile and antiproliferative effect of Ficus crocata extracts on triple-negative breast cancer cells - Carlos A. Sánchez-Valdeolívar; Patricia Alvarez-Fitz; Ana E. Zacapala-Gómez; Macdiel Acevedo-Quiroz; Lorena Cayetano-Salazar; Monserrat Olea-Flores; Jhonathan U. Castillo-Reyes; Napoleón Navarro-Tito; Carlos Ortuño-Pineda; Marco A. Leyva-Vázquez; Julio Ortíz-Ortíz; Yaneth Castro-Coronel; et al. (BMC, 2020)
Abstract Background Some species of the Ficus genus show pharmacological activity, including antiproliferative activity, in cell lines of several cancer Types. ficus crocata is distributed in Mexico and used in traditional medicine, as it is believed to possess anti-inflammatory, analgesic, and antioxidant properties. However, as of yet, there are no scientific reports on its biological activity. This study aims to evaluate the phytochemical profile of F. crocata leaf extracts and their effects on breast cancer MDA-MB-231 cells proliferation. Moreover, the study aims to unearth possible mechanisms involved in the decrease of cell proliferation. Methods The extracts were obtained by the maceration of leaves with the solvents hexane, dichloromethane, and acetone. The phytochemical profile of the extracts was determined using gas chromatography coupled with mass analysis. Cell proliferation, apoptosis, and cell cycle analysis in MDA-MB-231 cells were determined using a Crystal violet assay, MTT assay, and Annexin-V/PI assay using flow cytometry. The data were analyzed using ANOVA and Dunnett's test. Results The hexane (Hex-EFc), dichloromethane (Dic-EFc), and acetone (Ace-EFc) extracts of F. crocata decreased the proliferation of MDA-MB-231 cells, with Dic-EFc having the strongest effect. Dic-EFc was fractioned and its antiproliferative activity was potentiated, which enhanced its ability to induce apoptosis in MDA-MB-231 cells, as well as increased p53, procaspase-8, and procaspase-3 expression. Conclusions This study provides information on the biological activity of F. crocata extracts and suggests their potential use against triple-negative breast cancer.